Immediate complications of laparoscopic tubal sterilization: 11 Years of experience - Chaovisitsaree S. (2014)
Objective: To evaluate the complications of laparoscopic tubal sterilization. Method: A retrospective study of laparoscopic tubal sterilization performed at Maharaj Nakorn Chiang Mai Hospital, Faculty of Medicine, Chiang Mai, Thailand was conducted. The details of the operation, including complications and operation time were collected from the operative and family planning registry. Results: Between January 1987 and December 1997, 948 cases of laparoscopic tubal sterilization were performed as an outpatient setting. The combination of intravenous sedation and local anesthesia was employed in all cases. Minor infra-operative complications were found in 4.6% of cases. The most frequent complications were meso-salphingeal and meso-ovarian bleeding. No serious complication was found in this study. The mean operation time was 19.3 minutes (range 5-75 minutes). Conclusion: The present study suggested that out-patient laparoscopic tubal sterilization under the combination of intravenous sedation and local anesthesia is a convenient and relatively safe procedure.